Actividades socio-económicas y los aliados estratégicos en el turismo - Zuñiga Mayorga, Jazminia Eilee (2021)
The paralysis of the tourism sector due to the pandemic caused great economic losses in the country, families without sources of income, totally desolate tourist sectors, temporary and permanent closure of many businesses, all this generating great concerns in the tourism sector. With the arrival of the vaccine from several international pharmaceutical companies, tourism began to reactivate little by little, not with the same intensity as before, but with a 50% influx of tourists, reactivating the economy of the tourism sector in our country. The objective of this investigative work is to make known the socioeconomic activities and strategic allies in tourism. The techniques applied in the collection of information were the descriptive and quantitative methods for convenience, applying the online survey using the 5-question questionnaire as an instrument. With the help of the SSE (Social and Solidarity Economy), citizens can obtain ideas or seek new ways to generate income by obtaining marketing strategies from said organization, seeking a collective economy with all those who participate in it. Strategic allies provide the tourism sector with all the help they require to increase their income, and facilitate the process of serving tourists, such as science, technology and innovation that are necessary tools not to say essential in the century that we are living, all this in order to provide a quality service and that the tourist's stay is full and pleasant.